2009
DOI: 10.1017/s0032247408007511
|View full text |Cite
|
Sign up to set email alerts
|

Going native in the north: reconsidering British attitudes during the Franklin search, 1848–1859

Abstract: This article critically examines the assumption that the men of Sir John Franklin's last Arctic expedition died because, influenced by the characteristic British cultural prejudices of their time, they refused to employ Inuit survival skills. Since no detailed records from this expedition have ever been found, there is no direct evidence about the attitudes held or actions taken by its members. The article therefore draws on another source: the very extensive British periodical and newspaper coverage of the Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Rodahl, a generation later, drew similar conclusions. Essentially the early twentieth century studies of ‘Eskimo’ physiology and adaptation suggested that the practice of ‘going native’—as discussed by Cavell—of adapting indigenous practices and technologies, would render non-indigenous bodies as resistant to the cold as those of the permanent residents of the far North (Cavell 2009 ).…”
Section: Cold Is Technology; Heat Is Biologymentioning
confidence: 99%
“…Rodahl, a generation later, drew similar conclusions. Essentially the early twentieth century studies of ‘Eskimo’ physiology and adaptation suggested that the practice of ‘going native’—as discussed by Cavell—of adapting indigenous practices and technologies, would render non-indigenous bodies as resistant to the cold as those of the permanent residents of the far North (Cavell 2009 ).…”
Section: Cold Is Technology; Heat Is Biologymentioning
confidence: 99%
“…The expedition intended to procure as much game as possible (Bell 1881) and a possible shooting station was identified on King William Island by Hobson during McClintock's (1859) search (Stenton 2014) but it is unknown whether hunting was successful. Hobson travelled the shoreline from Cape Felix to Cape Herschel and concluded that ‘[t]here is not the slightest chance of a party subsisting by hunting on this shore, we saw no traces of deer or musk oxen’ (quoted by Stenton 2014: 519; and see Cavell 2009). However, in a personal communication, Dr D. Stenton, Director of Heritage, Government of Nunavut, has informed the authors that whilst game is scarce on the northwest coast of King William Island in winter and spring (Stenton, personal communication, 31 May 2015), Schwatka observed some seal and caribou in the area in late spring and summer and abundant game at that time on the south coast (see Klutschak 1987: 100–106).…”
Section: Scurvy and The Franklin Crewsmentioning
confidence: 99%
“…The expedition also endured lengthy entrapment in the pack ice, far from land that, in any case, probably could not provide sufficient game for their needs (Cavell 2009). The winters while beset are known to have been intensely cold (Alt and others 1985; Gilpin 1850) and therefore exposed the crews to greater risk of fatal accidents and of succumbing to exposure because operations away from the ships were made more arduous.…”
Section: Scurvy and The Franklin Crewsmentioning
confidence: 99%
“…When the cannibalism story broke in England in 1854, it provoked a range of responses. Many accepted that survival cannibalism was born out of tragic necessity, but others variously felt that it was unproven, rejected the possibility outright or else simply chose to ignore the evidence (Cavell, , ; Brandt, : 368‐372). These ambivalent attitudes continued well into the 20th century.…”
Section: Introductionmentioning
confidence: 99%